Fire performance of reinforced concrete frames using sectional analysis. (1st July 2017) - El-Fitiany, S.F.; Youssef, M.A.
Highlights: Structural behavior of RC frames during fire exposure is studied. Practical approach to analyze RC frames during fire exposure is developed. Expressions for unrestrained thermal deformations are developed. Expressions for effective stiffnesses of fire-exposed elements are developed. Abstract: Global behavior of RC structures during fire events can be predicted using complex nonlinear thermal-structural numerical simulations. However, such simulations are computationally expensive, which limit their use by design engineers. A practical approach to track the performance of RC frames during fire exposure is proposed and validated in this paper. A previously developed simple heat transfer technique is used to calculate an average 1D temperature distribution for heated RC sections. Consequently, the flexural and axial stiffnesses as well as the unrestrained thermal deformations are evaluated using sectional analysis. Based on rational assumptions, simplified expressions are also driven to evaluate those values. The proposed method can be easily applied using available commercial linear structural analysis software to predict the fire performance of RC framed structures. Additional experimental and analytical work is required to validate the proposed method in non-standard fire scenarios.